University Engagement with Farming Communities in Africa Community Action Research Platforms - Egeru, Anthony; Lindow, Megan; Muir Leresche, Kay (Earthscan Food and Agriculture, 2024)
This book explains and explores how collaborations can be built and strengthened between African universities and farming communities to address real-world contemporary challenges. The book focuses on Community Action Research Platforms, an approach that has successfully enabled African universities to break free of the ivory tower and prove their relevance to society through deep collaborative engagements in targeted agricultural value chains. Developed in a pan-African network of universities (RUFORUM) focused on capacity building in agriculture, the approach has been tested in diverse settings over the last 15 years. The book draws on the experiences and lessons from 21 different projects initiated by RUFORUM member universities in Benin, Botswana, Ethiopia, Ghana, Kenya, Malawi, Namibia, South Africa, Sudan, Tanzania, Uganda and Zimbabwe. It highlights a critical yet underutilised role for African universities as collaborators and catalysts for multisector solutions. These are solutions that increase productivity and address climate change. They develop livelihoods and resilience in rural communities, as well as promote farmers' access to markets, innovation and trade while safeguarding biodiversity and enhancing food and nutrition security. The book makes a case for repositioning African universities as fulcrums of development in society. It shares the rich experiences, learnings and scientific findings of diverse researchers, practitioners and students who have been working towards achieving this reality on the ground. This multidisciplinary book holds appeal for university leaders, higher education, agrifood and development specialists, researchers and practitioners, policymakers and development agencies engaged in African agriculture and rural development, higher education and sustainable growth.